The Ionospheric Impact of an ICME‐Driven Sheath Region Over Indian and American Sectors in the Absence of a Typical Geomagnetic Storm. Issue 5 (23rd May 2018) - Rout, Diptiranjan; Chakrabarty, D.; Sarkhel, S.; Sekar, R.; Fejer, B. G.; Reeves, G. D.; Kulkarni, Atul S.; Aponte, Nestor; Sulzer, Mike; Mathews, John D.; Kerr, Robert B.; Noto, John
Abstract: On 13 April 2013, the ACE spacecraft detected arrival of an interplanetary shock at 2250 UT, which is followed by the passage of the sheath region of an interplanetary coronal mass ejection (ICME) for a prolonged (18‐hr) period. The polarity of interplanetary magnetic field Bz was northward inside the magnetic cloud region of the ICME. The ring current (SYM‐H) index did not go below −7 nT during this event suggesting the absence of a typical geomagnetic storm. The responses of the global ionospheric electric field associated with the passage of the ICME sheath region have been investigated using incoherent scatter radar measurements of Jicamarca and Arecibo (postmidnight sector) along with the variations of equatorial electrojet strength over India (day sector). It is found that westward and eastward prompt penetration (PP) electric fields affected ionosphere over Jicamarca/Arecibo and Indian sectors, respectively, during 0545–0800 UT. The polarities of the PP electric field perturbations over the day/night sectors are consistent with model predictions. In fact, DP2‐type electric field perturbations with ∼40‐min periodicity are found to affect the ionosphere over both the sectors for about 2.25 hr during the passage of the ICME sheath region. This result shows that SYM‐H index may not capture the full geoeffectivenss of the ICME sheath‐driven storms and suggests that the PP electric field perturbations should be evaluated for geoeffectiveness of ICME when the polarity of interplanetary magnetic field Bz is northward inside the magnetic cloud region of the ICME. Key Points: Effects of ICME sheath region is observed on equatorial ionosphere in the absence of a typical storm Prompt penetration electric field can capture the geoeffectiveness of an ICME event The geoeffectivenss of an ICME can be efficiently evaluated by the PP/OS electric field effects on the global ionosphere